Anti-Inflammatory Activity of Delonix regia (Boj. Ex. Hook) - Vaishali D. Shewale; Tushar A. Deshmukh; Liladhar S. Patil; Vijay R. Patil (Hindawi Limited, 2012)
The present work was to evaluate the anti-inflammatory activity of Delonix regia leaves (Family: Caesalpiniaceae). The powder of Delonix regia leaves was subjected to extraction with ethanol in soxhlet extractor. The ethanol extract after preliminary phytochemical investigation showed the presence of sterols, triterpenoids, phenolic compounds and flavonoids. The anti-inflammatory activity was studied using carrageenan-induced rat paw edema and cotton pellet granuloma at a three different doses (100, 200, and 400 mg/kg b.w. p.o.) of ethanol extract. The ethanol extract of Delonix regia leaves was exhibited significant anti-inflammatory activity at the dose of 400 mg/kg in both models when compared with control group. Indomethacin (10 mg/kg b.w. p.o) was also shown significant anti-inflammatory activity in both models.